Effect of Increasing Sea Water Temperature on Performance of Steam Turbine of Muara Tawar Power Plant - Nastopo Darmawan; Triyogi Yuwono (IPTEK The Journal for Technology and Science, 2019)
Muara Tawar Power Plant is located on the coast of Bekasi, West Java, Indonesia. Along with the economic development, there are plans to do reclamation the sea around Muara Tawar Power Plant and build around it as a port and industrial estate. This could potentially lead to an increase in sea water temperatures. This paper aims to determine the effect of increasing sea water temperature on the performance of steam turbine 1.4 in Muara Tawar Power Plant, which uses sea water as a condenser cooling medium. The intended performance is the output power of the steam turbine, the condenser pressure and the system efficiency. Steam turbine 1.4 has 225 MW installed output power, supplied from 3 HRSG (Heat Recovery Steam Generator).Analysis of the effect of sea water temperature rise on steam turbine performance is carried out by using the cycle-tempo software. The main equipment of steam turbine is modeled in cycle-tempo, then model is validated by comparing with design data. Varies sea water temperature then is inputted on model in order to obtain the output power of steam turbine, condenser pressure and system efficiency. The results show that for every 1˚C increase in condenser cooling water temperature extracted from seawater near the plant, the output power of the plant decreased by about 0.171%, the condenser pressure increased by about 5.146%, and the system efficiency decreased by about 0.168%.